Efeitos da eletroestimulação transcutânea do nervo tibial e região parassacral em mulheres com urgência miccional: estudo randomizado e controlado - Padilha, Juliana Falcão (2021)
Introduction: Urgency is a strong urge to urinate, which is difficult to postpone and control. Urgency urinary incontinence is the involuntary loss of urine associated with urgency and the overactive bladder is characterized by urgency with or without urinary loss. These are common clinical conditions in women. One of the physiotherapeutic resources that can be used to treat urgency is electrostimulation, such as electrostimulation of the tibial nerve and parasacral electrostimulation. Objective: To investigate the effect of treatment with transcutaneous electrostimulation of the Tibial Nerve or transcutaneous parasacral electrostimulation on urgency. Methods: 99 women, over the age of 18, with a score ≥8 on the Overactive Bladder –Validated 8 - Question Awareness Tool [OAB-V8]), participated in the study, randomized (1:1:1) using a simple draw in 3 groups: 33 in the placebo group, 33 in the tibial group and 33 in the parasacral group. In the tibial and parasacral groups, a frequency of 10Hz was applied and the pulse duration was 200μs. In the placebo group (electrostimulation in the scapular region), a frequency of 100Hz was applied and pulse duration was 100μs. The intensity varied according to the sensitivity of the participant for all groups. Outcome measures: The outcomes were assessed by the International Consultation on Incontinence Questionnaire - Overactive Bladder (ICIQ-OAB), which assesses overactive bladder and investigates irritative urinary symptoms such as daytime frequency, nocturia, urgency and urgent urinary incontinence; Overactive Bladder –Validated 8 - Question Awareness Tool (OAB-V8), which investigates overactive bladder and measures the degree of discomfort, based on the self-perception of the participant; King Health Questionnaire (KHQ), which investigates quality of life in relation to urinary incontinence; and 24-hour Voiding Diary (VD-24h), which investigates voiding habits. The evaluations occurred in four moments: pre-treatment, after the 6th session, after the 12th session (post-treatment) and follow-up (30 days after the end of the treatment). Statistical analysis: Two-way ANOVA for repeated measures was applied to verify the effect of groups, evaluations, and interactions, in the total scores of the ICIQ-OAB, OAB-V8, in the KHQ domains and in the VD-24h variables. In the case of normality of the residues of the ANOVA model, the parametric approach with post-hoc was used by the Bonferroni test. Otherwise, the post-hoc non-parametric approach was used by the Anova-Type Statistic test with Bonferroni correction. The normality of the residues was assessed by the Shapiro-Wilk test. A significance level of 5% was considered. Results: The parassacral and tibial groups, in the post-treatment, presented fewer episodes of urgency than the placebo group (evaluated by the VD-24h). In the follow-up, the parassacral group presented a superior result than the placebo group in the ICIQ-OAB. In the post-treatment, the parassacral group obtained significantly greater results than the placebo group in the domains of incontinence impact and task limitations of the KHQ. Conclusion: In the present study, the number of urgency episodes evaluated by the VD-24h after treatment, showed that the parassacral and tibial groups had better results than the placebo group. Parasacral electrostimulation was more effective in reducing urgency compared to placebo, which is observed by the significant decrease in the total ICIQ-OAB score, at follow-up.